Feasibility study on utilization of palm fibre waste into fired clay brick - A. Kadir, A.; Sarani, N. A.; Zaman, N. N.; Abdullah, Mohd Mustafa Al Bakri (American Institute of Physics, 2017)
Malaysia is the second largest of palm oil producer after Indonesia, which contribute to 50 % of palm oil production. With this demand, the increasing of palm oil plantation over the years has led to the large production of agricultural waste, for example palm fibre waste. This study investigates different percentages of palm fibre (0 %, 1 %, 5 % and 10 %) to be incorporated into fired clay brick. Manufactured bricks were fired at 1 °C/min heating rate up to 1050 °C. The effects of manufacture bricks on the physical and mechanical properties of manufactured brick were also determined. All brick samples were tested due to the physical and mechanical properties which include dry density, firing shrinkage, initial rate of suction (IRS), water absorption, porosity and compressive strength. Findings show that increasing palm fibre waste affected the properties of brick, which decreased their density, besides increased firing shrinkage, IRS, water absorption, porosity and compressive strength. However, all the manufactured brick still followed the requirement.